Control of third-order nonlinear optical properties by coordination metal change based on a series of metal organic chains. (15th July 2020) - Yang, Xiaoqian; Shao, Zhichao; Zhao, Yujie; Xie, Qiong; Meng, Xiangru; Song, Yinglin; Hou, Hongwei
Graphical abstract: The change of the third-order NLO performances is due to the coordination bond between metal ions and the ligand, which changes the delocalization of the entire system. Abstract: The research on the third-order nonlinear optics (NLO) materials have attracted more and more attention. In this work, an organic ligand (H2 L) containing azo phenyl group and coordination N atom is selected. The presence of NN increases the fluidity of electrons in the azo molecule, which greatly improves the third-order nonlinearity. Furthermore, we synthesized three H2 L-based metal complexes [Mn(L)(H2 O)4 ]n (1 ), [Zn(L)(H2 O)2 ]n (2 ) and [Cd(L)(H2 O)4 ]n (3 ) and their nonlinear performances was also measured using Z-scan technology. The results show that the coordination bond between metal ions and the ligand changes the delocalization of the whole systems, resulting in changed the nonlinear performances. The calculation of density functional theory (DFT) confirms that the Mn 2+ and Zn 2+ addition is not obvious to influence NLO, and the addition of Cd 2+ makes the non-linear signal weaken. The reason may result from the valence layer electron configuration of the different metal ions.